Liver stiffness by transient elastography accompanies illness severity in COVID-19. Issue 1 (13th July 2020) - Effenberger, Maria; Grander, Christoph; Fritsche, Gernot; Bellmann-Weiler, Rosa; Hartig, Frank; Wildner, Sophie; Seiwald, Stefanie; Adolph, Timon Erik; Zoller, Heinz; Weiss, Gunter; Tilg, Herbert
Abstract : Objective: Severe liver damage is associated with worse outcome in COVID-19. Our aim was to explore the degree of liver damage, liver stiffness (LS) and severity of illness in patients with COVID-19. Design: We investigated 32 patients with COVID-19 admitted to the University Hospital of Innsbruck in a prospective cross-sectional study. We performed laboratory testing, liver and spleen sonography and elastography to measure organ stiffness. Results: 12 patients (38%) showed elevated aminotransferases and gamma-glutamyltransferase levels. LS was positively correlated with elevated aminotransferase levels in patients with COVID-19 compared with those without elevated enzymes. Even mild liver damage raised LS significantly in COVID-19 as it was in patients with gastrointestinal symptoms. Furthermore, higher LS measurements were significantly associated with illness severity like pneumonia, need for mechanical ventilation, and even death. Conclusion: Transient elastography is a useful and non-invasive tool to assess onset and severity of acute liver injury in patients with COVID-19 patients. Increased LS seems to be predictive for a more severe and complicated course of disease.